Gibberellin Deficiency Confers Both Lodging and Drought Tolerance in Small Cereals - Plaza-Wüthrich, Sonia; Blösch, Regula; Rindisbacher, Abiel; Cannarozzi, Gina; Tadele, Zerihun (Frontiers in Plant Science, 2016)
Tef [Eragrostis tef (Zucc.) Trotter] and finger millet [Eleusine coracana Gaertn] are staple cereal crops in Africa and Asia with several desirable agronomic and nutritional properties. Tef is becoming a life-style crop as it is gluten-free while finger millet has a low glycemic index which makes it an ideal food for diabetic patients. However, both tef and finger millet have extremely low grain yields mainly due to moisture scarcity and susceptibility of the plants to lodging. In this study, the effects of gibberellic acid (GA) inhibitors particularly paclobutrazol (PBZ) on diverse physiological and yield-related parameters were investigated and compared to GA mutants in rice (Oryza sativa L.). The application of PBZ to tef and finger millet significantly reduced the plant height and increased lodging tolerance. Remarkably, PBZ also enhanced the tolerance of both tef and finger millet to moisture deficit. Under moisture scarcity, tef plants treated with PBZ did not exhibit drought-related symptoms and their stomatal conductance was unaltered, leading to higher shoot biomass and grain yield. Semi-dwarf rice mutants altered in GA biosynthesis, were also shown to have improved tolerance to dehydration. The combination of traits (drought tolerance, lodging tolerance and increased yield) that we found in plants with altered GA pathway is of importance to breeders who would otherwise rely on extensive crossing to introgress each trait individually. The key role played by PBZ in the tolerance to both lodging and drought calls for further studies using mutants in the GA biosynthesis pathway in order to obtain candidate lines which can be incorporated into crop-breeding programs to create lodging tolerant and climate-smart crops.